Wonder - Palacio, R. J. (New York : Knopf, 2014)
Ten-year-old Auggie Pullman, who was born with extreme facial abnormalities and was not expected to survive, goes from being home-schooled to entering fifth grade at a private middle school in Manhattan, which entails enduring the taunts and fear of his classmates as he struggles to be seen as just another student.
Booklist starred
Library Media Connection starred
School Library Journal starred
Booklist starred, February 2012
Bulletin (Center for Children's books), March 2012
Horn Book, July 2012
Keywords: Abnormalities, Human -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Self-acceptance -- Juvenile fiction; Abnormalities, Human -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Self-acceptance -- Fiction; Birth defects -- Fiction; Middle schools -- Fiction; School stories; Self-acceptance -- Fiction